Analisis Kuantitatif Formalin pada Buah Impor pada Swalayan di Kota Banda Aceh - Syahrizal Syahrizal (AcTion: Aceh Nutrition Journal, 2016)
The low national production force people to consume fruits imports. Fruit imports have good physical qualities but let not suitable for consumption because it contains a variety of harmful substances, ie formalin. The study aims to quantitatively analysis the formaldehyde content in imported fruit. Design research is descriptive and analytical, with the object of research Supermarkets in Banda Aceh, while the sample of citrus fruits, grapes, and apples. Tests conducted formalin test laboratory with spectrophotometric. The results of the study showed that inspected fruits (apples, grapes, and oranges) positive for formaldehyde formaldehyde formaldehyde levels> 8.00 mg/liter. The conclusion that although the fruits are sold in supermarkets in the city of Banda Aceh positive for formaldehyde, but the content is still in early stages of normal (but still within the threshold value), in addition to the physical quality of the fruit is still in a fresh condition. Suggestions need to tighten supervision of the entry of fruit imported into the country in anticipation of for containing hazardous substances, and for the Food and Drug Control to conduct monitoring of the use of formaldehyde in self-self-service. Keywords:  Fruits, formalin, physical qualities of fruit